The Influence Of E-WOM On Purchase Intention With Brand Image As A Mediator Variable - Sylvia, Sylvia; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research is a quantitative research with a causal relationship to determine the direct effect of eWOM and Brand Image on Purchase Intention and to determine the indirect effect of eWOM on Purchase Intention through the Brand Image of skincare products something. Data collection was carried out by collecting information through a survey with a questionnaire. The population in this study is someone who already knows the Something skincare product in the Jabodetabek area. The questionnaire collected 110 respondents using the Hair et al., (2017) formula. The questionnaire collected was 110 respondents, the data was then processed using the SmartPLS analysis tool. The sampling method used is non-probability sampling with purposive sampling technique. Based on the research results, 4 hypotheses can be accepted, namely eWOM has an effect on Brand Image, eWOM has an effect on Purchase Intention, Brand Image has an effect on Purchase Intention, Brand Image has an effect on mediating eWOM and Purchase Intention. The contribution of this research resulted in increased awareness of eWOM with the influencing factors, namely Brand Image and Purchase Intention. Therefore, it is important for Something's product to increase brand image awareness from the influence of electronic word of mouth which can increase interest in buying the product. The purpose of this study was to determine the direct effect of E-WOM, Brand Image and Purchase Intention and also to determine the indirect effect of E-WOM, Brand Image and Purchase Intention shown to consumers of Something skincare products. Keywords: Electronic Word Of Mouth, Brand Image, Purchase Intention